Chemical control of continuous light-steering using an array of gradient Au/Bi2Se3/Au strips. Issue 85 (16th September 2015) - Cao, Tun; Zheng, Guangzhao; Wang, Shuai
<x xml:space="preserve">Abstract</x> Achievement of continuous light-steering in an array of gradient Au/Bi2Se3/Au strips by modulating the dielectric function of Bi2Se3.